Measurement of the tt̄ production cross section in pp̄ collisions at s=1.96TeV in the all hadronic decay mode - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2006)
We report a measurement of the tt̄ production cross section using the CDF II detector at the Fermilab Tevatron. The analysis is performed using 311pb-1 of pp̄ collisions at s=1.96TeV. The data consist of events selected with six or more hadronic jets with additional kinematic requirements. At least one of these jets must be identified as a b-quark jet by the reconstruction of a secondary vertex. The cross section is measured to be σtt̄=7. 5±2.1(stat.)-2.2+3.3(syst.)-0.4+0.5(lumi.)pb, which is consistent with the standard model prediction. © 2006 The American Physical Society.